A new species in the genus Circinaria (Lichenized Ascomycetes: Megasporaceae) from Pakistan - Zulfiqar, Rizwana; Habib, Kamran; Asghar, Hafiza Simab; Wahab, Hira; Sohrabi, Mohammad; Paukov, Alexander G.; Ren, Qiang; Khalid, Abdul Nasir (Phytotaxa, 2024)
A crustose species Circinaria semicontorta is described here as new to science. It is characterized by a whitish areolate to subverrucose thallus with a thinning, cracked margin, not forming true lobes, areoles with raised whitish pseudocyphellae containing black ostioles of conidiomata, and long pycnoconidia, 12–25 μm. The phylogenetic analysis based on ITS sequences confirms placing the new species within Circinaria.